2019
DOI: 10.1039/c9ob01471c
|View full text |Cite
|
Sign up to set email alerts
|

Modifications of amino acids using arenediazonium salts

Abstract: Aryl transfer reactions from arenediazonium salts have started to make their impact in chemical biology with initial forays in the arena of arylative modifications and bio-conjugations of amino acids, peptides and proteins.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
49
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(52 citation statements)
references
References 209 publications
3
49
0
Order By: Relevance
“…The resulting products were isolated and triazenation of secondary amines was confirmed by NMR ( 1 H and 13 C) (Supplementary Figure 3). In contrast, no product was observed with alanine, thus reconfirming literature reports that the formation of the triazene‐coupling product with primary amine is reversible in nature (Supplementary Figure 4) [37, 38] …”
Section: Resultssupporting
confidence: 80%
“…The resulting products were isolated and triazenation of secondary amines was confirmed by NMR ( 1 H and 13 C) (Supplementary Figure 3). In contrast, no product was observed with alanine, thus reconfirming literature reports that the formation of the triazene‐coupling product with primary amine is reversible in nature (Supplementary Figure 4) [37, 38] …”
Section: Resultssupporting
confidence: 80%
“…The multimodal reactivity of aryldiazonium salts can be exploited to modify a wide range of amino acids, [63] including Tyr. Aryldiazonium salts, generally prepared from the corresponding anilines by action of a nitrite in a strong acid medium, can establish an azo linkage with the phenol side ring of Tyr by an electrophilic aromatic substitution (Figure 12).…”
Section: Diazonium Coupling Reactionmentioning
confidence: 99%
“…71,86 In these protocols, the nucleophilic cysteine thiol was modified with organopalladium, organogold reagents, 87 boronic acids, 88 or diazonium salts. 89 As a complementary strategy representing an inverse approach, we envisioned that Ala Sn could be used to introduce aryl (seleno)cysteine with redox-neutral electrophiles such as Nsulfenylsuccinimides 20 or diselenides 21 (Scheme 4B). We found that the cross-coupling of Ala Sn could be catalyzed by in 71% without epimerization at the α-carbonyl.…”
Section: Introductionmentioning
confidence: 99%